Global biogeographic distribution of Bathyarchaeota in paddy soils - Shu-Dan Xue; Xing-Yun Yi; Hui-Ling Cui; Meng Li; Jing-Jing Peng; Yong-Guan Zhu; Gui-Lan Duan (mSystems, 2023)
ABSTRACT Bathyarchaeota, known as key participants of global elements cycling, is highly abundant and diverse in the sedimentary environments. Bathyarchaeota has been the research spotlight on sedimentary microbiology; however, its distribution in arable soils is far from understanding. Paddy soil is a habitat similar to freshwater sediments, while the distribution and composition of Bathyarchaeota in paddy soils have largely been overlooked. In this study, we collected 342 in situ paddy soil sequencing data worldwide to illuminate the distribution patterns of Bathyarchaeota and explore their potential ecological functions in paddy soils. The results showed that Bathyarchaeota is the dominant archaeal lineage, and Bathy-6 is the most predominant subgroup in paddy soils. Based on random forest analysis and construction of a multivariate regression tree, the mean annual precipitation and mean annual temperature are identified as the factors significantly influencing the abundance and composition of Bathyarchaeota in paddy soils. Bathy-6 was abundant in temperate environments, while other subgroups were more abundant in sites with higher rainfall. There are highly frequent associations between Bathyarchaeota and methanogens and ammonia-oxidizing archaea. The interactions between Bathyarchaeota and microorganisms involved in carbon and nitrogen metabolism imply a potential syntrophy between these microorganisms, suggesting that members of Bathyarchaeota could be important participants of geochemical cycle in paddy soils. These results shed light on the ecological lifestyle of Bathyarchaeota in paddy soils, and provide some baseline for further understanding Bathyarchaeota in arable soils. IMPORTANCE Bathyarchaeota, the dominant archaeal lineage in sedimentary environments, has been the spotlight of microbial research due to its vital role in carbon cycling. Although Bathyarchaeota has been also detected in paddy soils worldwide, its distribution in this environment has not yet been investigated. In this study, we conducted a global scale meta-analysis and found that Bathyarchaeota is also the dominant archaeal lineage in paddy soils with significant regional abundance differences. Bathy-6 is the most predominant subgroup in paddy soils, which differs from sediments. Furthermore, Bathyarchaeota are highly associated with methanogens and ammonia-oxidizing archaea, suggesting that they may be involved in the carbon and nitrogen cycle in paddy soil. These interactions provide insight into the ecological functions of Bathyarchaeota in paddy soils, which will be the foundation of future studies regarding the geochemical cycle in arable soils and global climate change.